EVALUATION OF THE STRUCTURAL BEHAVIOR OF ALUMINUM HONEYCOMB SANDWICH PANELS FOR MICROSATELLITES (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work has as target the analysis of honeycomb structures by applying analytical models and numerical simulation that employ different finite element approaches: solid model for panel with equivalent honeycomb core properties, solid model of the honeycomb core and faces, and surface model of the honeycomb core and faces. There is also the standard test method for determination of the bending and shear properties of honeycomb sandwich samples whose results are employed for validation purposes. Thus, the main interest is to study the deformation of the honeycomb structures under shear load to devise a methodology to facilitate their design and manufacture. The prediction of the structural behavior of satellite components at real conditions of operation as well as the quality assessment of their manufacturing process requires this preliminary stress-strain evaluation of honeycomb sandwich panel samples. In this work, several tests were performed to access the behavior of the honeycomb structures and the results are consistent to the literature.